Boas práticas agropecuárias sobre a produção, a composição e qualidade de leite em rebanhos mestiços - Suely de Jesus Oliveira (2016)
We aimed to evaluate the effect of implementation of good agricultural practices in milk quality crossbred herds over 5 years on the production, composition and quality of milk. The work was carried out analysis of data obtained from dairy farms in the municipalities of Janaúba, Porteirinha, Serranópolis Minas, São João da Lagoa and Jaíba, Northern Minas Gerais, from January 2008 to December 2012, where samples of all raw milk were collected questionnaires and conducted tests California Mastitis Test (CMT) in dairy cows. For description and better understanding of the data, we calculated the average of each variable response property, year, season and month. months properties and cluster analysis were performed considering the output characteristics to define similarities between groups. It conducted multiple correspondence analysis in an attempt to establish an association between climate variables, flock, good management practices and production characteristics, composition and quality of milk, and these variables were categorized in class.Estimates of linear associations between variables production and quality were obtained by Pearson correlation.Risk factors for increasing somatic cell count (CCS) > 400,000 cells mL-1 and total bacterial count (CBT) )> 100,000 cfu mL-1 were obtained by logistic regression. CCS and CBT were categorized considering milk payment police. The non-adoption of the milking line causes the chance of milk to be CCS> 400,000 cells mL-1 16.42 times greater than when it is adopted. The risk of CBT to be greater than > 100,000 cfu mL-1 is 12.59 times greater when paper towels are not used for cleaning teats. The practices adopted all year long were efficient to maintain milk quality even in higher rainfall seasons. Milking practices as, milking line, sanitization of environment and utilization of disposable materials for cleaning teats in pre-milking procedures, are effective to prevent greater risk of CCS and CBT increasing. Moreover economic losses can be avoided once lower price is paid for poor quality milk.